The Influence of Learning Methods and Learning Interest on Environmental Knowledge and Awareness - Nurdin Nurdin; Tjipto Djuhartono; Harsono; Imam Suseno; Imam Suseno; Ani Interdiana Candra Sari (Journal for Lesson and Learning Studies, 2026)
Low environmental awareness knowledge among students remains a problem in learning because the instructional process is still teacher-centered and does not actively engage students. In addition, differences in students’ learning interest cause variations in the effectiveness of learning methods, making it necessary to implement instructional strategies that align with students’ characteristics. This study aimed to analyze and examine the influence of learning methods and learning interest on students’ environmental awareness knowledge. The study employed a quasi-experimental method with a 2 × 2 factorial design. The research subjects consisted of 80 twelfth-grade students, including 40 students with high learning interest and 40 students with low learning interest. Data were collected through an environmental awareness knowledge test and a learning interest questionnaire. The data were analyzed using two-way analysis of variance (ANOVA) followed by the Tukey test to identify differences among groups. The findings revealed that the cooperative learning method was more effective than the discussion method in improving students’ environmental awareness knowledge. However, the discussion method was more suitable for students with high learning interest, whereas the cooperative learning method was more effective for students with low learning interest. This study concludes that the effectiveness of learning methods is influenced by students’ learning interest; therefore, selecting appropriate instructional strategies can support the improvement of environmental awareness knowledge more optimally.